Missed Opportunities for Vaccination in the Dominican Republic: Results of an Operational Investigation - Garib, Zacarías (Biomed Res Int, 2016)
Background. Despite the success of the Dominican Republic's National Immunization Program, homogenous vaccine coverage has not been achieved. In October 2012, the country implemented a study on missed opportunities for vaccination (MOVs) in children aged <5 years. Methods. A cross-sectional study of 102 healthcare facilities was implemented in 30 high-risk municipalities. Overall, 1500 parents and guardians of children aged <5 years were interviewed. A MOV is defined as when a person who is eligible for vaccination and with no contraindications visits a health facility and does not receive a required vaccine. We evaluated the causes of MOVs and identified risk factors associated with MOVs in the Dominican Republic. Results. Of the 514 children with available and reliable vaccination histories, 293 (57.0%) were undervaccinated after contact with a health provider. Undervaccinated children had 836 opportunities to receive a needed vaccine. Of these, 358 (42.8%) qualified as MOVs, with at least one MOV observed in 225 children (43.7%). Factors associated with MOVs included urban geographic area (OR = 1.80; p = 0.02), age 1–4 years (OR = 3.63; p ≤ 0.0001), and the purpose of the health visit being a sick visit (OR = 1.65; p = 0.02). Conclusions. MOVs were associated primarily with health workers failing to request and review patients' immunization cards.